Life on the Rainforest Edge: Food Security in the Agricultural-Forest Frontier of Cross River State, Nigeria - Friant, Sagan; Ayambem, Wilfred A.; Alobi, Alobi O.; Ifebueme, Nzube M.; Otukpa, Oshama M.; Ogar, David A.; Alawa, Clement B. I.; Goldberg, Tony L.; Jacka, Jerry K.; Rothman, Jessica M. (Frontiers in Sustainable Food Systems, 2019)
A growing body of evidence demonstrates the importance of forests and wild animal-based foods for diets within tropical environments. However, deforestation and associated land-use changes can have competing effects on nutrition and food security as communities reorient from wild food use and subsistence-based agriculture to import/export markets. This research examines dietary differences and associated changes in food security during intermediate stages of deforestation and market integration in the agriculture-forest frontier of Cross River State, Nigeria. We used participant responses to mixed-methods interviews (n = 528) in six communities to measure individual dietary diversity, household food access, and short-term nutritional status, with specific attention to animal-based foods and the cultural and economic values attached to them, in two interior forest (n = 177) and four forest-edge (n = 351) communities. Multivariate analysis of dietary compositions revealed differences in food categories and types of meat consumed between forest environments. People in forest-edge communities reported consuming less bushmeat and dark green leafy vegetables, and more pulses, domestic meat, fish, eggs, dairy, other vegetables, sweets, condiments, and non-red palm oil compared to interior forest communities. Bushmeat was highly preferred and had more economic value than other animal-based foods, regardless of location. Forest-edge communities had fewer households involved in bushmeat related activities, and fewer hunters per household. However, traders in forest-edge communities sold a larger proportion of meat to people outside of the community than did traders in interior forest communities. Measures of nutrition and food security, but not wealth, improved in relation to dietary patterns in forest-edge communities compared to interior forest communities. Our results may reflect a “best of both worlds” scenario during the intermediate stages of deforestation and agricultural expansion near forested areas, where people have access to forest resources, increased ability to capitalize on forest goods, and access to market goods as they become integrated into market economies. Understanding the dietary consequences of environmental change is important, as food-related experiences may shape the trajectories of livelihood practices and landscape changes in tropical forests of biodiversity significance.